Strategi Pembelajaran Langsung pada Ekstrakurikuler Paduan Suara di SMP Negeri 4 Sewon - Maria Angelina Dowa; Agustina Ratri Probosini; Nur Arif Anandhita (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Learning strategies are a series of instructional actions that teachers must carry out in order for learning objectives to be achieved efficiently. The learning strategies used in the choir extracurricular activities at SMP Negeri 4 Sewon include direct learning strategies, indirect learning strategies, and inquiry-based learning strategies, utilizing demonstration, imitation, and drill methods.This research uses a qualitative method with a case study approach. The object of the research is the learning strategies employed in choir extracurricular activities, with the research subjects being the extracurricular teacher and students. Data collection techniques include observation, interviews, documentation, and literature study. Data validation is carried out using source triangulation and technique triangulation. Data analysis is conducted through data collection, data reduction, data presentation, and data verification. The results of the study show that the implementation of learning strategies in the choir extracurricular activities at SMP Negeri 4 Sewon uses demonstration, imitation, and drill methods in a structured and effective manner. These methods are combined with direct, indirect, and inquiry-based learning strategies to enhance students' vocal skills and creativity. The impact of implementing these strategies is an improvement in singing ability, the development of self-confidence, creativity, and independence, as well as increased student motivation to actively participate in choir activities. The teacher acts as a facilitator who creates a space for independent and collaborative learning, making the learning process more enjoyable. This activity not only develops musical skills but also builds students' confidence and professionalism in various performance opportunities. With regular practice schedules and relevant song material, this extracurricular activity makes a positive contribution to the development of students' talents and character at school.